Experimental Studies on Sugar Cane Bagasse Ash based Geomaterials - Nikhade H.R.; Dr. B. Ram Rathan Lal (International Journal of Engineering and Management Research, 2021)
Use of conventional materials is increasing day by day due to rapid infrastructural growth which increases the cost of materials and increases the cost of construction. Hence utilization of Sugar cane bagasse ash waste materials without causing threat to environment solves the problems of disposal and also can provide economical materials. In this study glass fiber, sugarcane bagasse ash and blast furnace slag were used and cement used for binding purpose. Different mix ratio was prepared to understand the effect of addition of glass fibre on sugar cane bagasse ash based materials under compressive loading. The mix ratio was taken 0.2 to 1.0% for the research work. Blast furnace slag was added 10% to weight of sugar cane bagasse ash. The sample were tested for compressive loading for 7, 14, 28 days respectively. The density is most important parameter of materials. It was observed that the density of materials significantly influences with addition of glass fibre. The density of materials decreases with percentage of glass fiber increase. The density of materials varies between 901.1 kg/m3 to 741.10kg/m3The compressive strength also significantly affected by percentages of glass fibre. The compressive strength ranging 82 kPa to 798 kPa.The compressive strength increases up to certain mix ratio then decrease continuously. The stiffness of sugar cane bagasse ash specimens reinforced with glass fiber at cement 20% more than 15% and 10%.The stiffness also increase with the curing period. The maximum load was observed at 0.6% mix ratio. The stress strain behavior was observed to be nonlinear.